ANALISIS GAMBARAN PERILAKU REMAJA PUTRI DALAM UPAYA PENCEGAHAN STUNTING MELALUI KONSUMSI TABLET TAMBAH DARAH DI SMK MUHAMMADIYAH 1 RANGKASBITUNG - Yulica Aridawarni; Neng Yara (Prodi DIII Kebidanan La Tansa Mashiro, 2025)
The purpose of this study was to determine the description of adolescent girls’ behavior in preventing stunting through the consumption of iron supplement tablets (TTD), to identify obstacles and motivations in consuming TTD, and to analyze the role of family, peers, school, and health workers in supporting TTD consumption at SMK Muhammadiyah 1 Rangkasbitung. This research used a descriptive method with a purposive sampling technique involving 13 adolescent girls aged 15–18 years. Data were collected through interviews and analyzed using univariate analysis.The results showed that most adolescent girls (76.9%) regularly consumed TTD, although some were still irregular. The main obstacles included the unpleasant taste of the tablets (61%) and lack of information (38%). The level of motivation was quite high, as participants wanted to prevent anemia and stunting, supported by families, teachers, peers, and health workers.In conclusion, the behavior of adolescent girls in consuming TTD was generally good but still needs improvement through education and continuous support from the surrounding environment so that it becomes a sustainable habit. Adolescent girls, iron supplement tablets, stunting prevention, health behavior.